Analisis Peran Akuntansi Syariah Untuk Transparansi Dan Keberlanjutan Ekonomi Lembaga Pembiayaan Syariah Baitul Maal Wa Tamwil (BMT) Mitra Khazanah Palembang - Muhammad Rafly; Delvi Ramadani; Bella Puspita Sari; Peny Cahaya Azwari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This research explores the important role of sharia accounting in improving transparency and economic sustainability at BMT Mitra Khazanah Palembang, an Islamic microfinance institution. Use descriptive qualitative method and literature study, this research shows that the implementation of sharia accounting significantly improves the transparency of financial statements and strengthens the trust of members and the community. In addition, sharia accounting also plays a role in promoting economic sustainability by ensuring the institution's financial activities are run in accordance with the principles of fairness, transparency, and social responsibility. Nevertheless, this study also identified several obstacles, such as limited human resources and information systems that have not been optimized. Therefore, this study emphasizes the importance of strengthening the capacity and commitment of institutions to implement Islamic accounting thoroughly and consistently.